Ordered Sp metric spaces and some fixed point theorems for contractive mappings with application to periodic boundary value problems - Z. Mustafa (14153358) (2019)
In this paper, we introduce the structure of Sp -metric spaces as a generalization of both S-metric and Sb -metric spaces. Also, we present the notions of S̃-contractive mappings in the setup of ordered Sp -metric spaces and investigate the existence of a fixed point for such mappings under various contractive conditions. We provide examples to illustrate the results presented herein. An application to periodic boundary value problems is presented. Other Information Published in: Fixed Point Theory and Applications License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1186/s13663-019-0666-3